20 ans d’e-Rea : des chiffres… et des textes - Grégoire LACAZE (E-REA)
As we celebrate the 20th anniversary of the digital journal e-Rea, this paper aims to look back to the issues of this journal from a statistical perspective. It analyses significant data and figures such as the quantity of published articles or book reviews, with a view to shedding light on editorial choices as seen over the years in the emergence of new sections. Visitor statistics highlight the internationalization of the journal and its increasing visibility in the field of English studies.